2008
DOI: 10.3748/wjg.14.5945
|View full text |Cite
|
Sign up to set email alerts
|

Role of sex steroid receptors in pathobiology of hepatocellular carcinoma

Abstract: The striking gender disparity observed in the incidence of hepatocellular carcinoma (HCC) suggests an important role of sex hormones in HCC pathogenesis. Though the studies began as early as in 1980s, the precise role of sex hormones and the significance of their receptors in HCC still remain poorly understood and perhaps contribute to current controversies about the potential use of hormonal therapy in HCC. A comprehensive review of the existing literature revealed several shortcomings associated with the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
118
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(132 citation statements)
references
References 146 publications
13
118
1
Order By: Relevance
“…43 However, the transition of IHCA into HCC and thus tumor initiation is not frequently found. 47 In the present study, we observed a reduction in the DENinduced HCC load in gp130…”
Section: 43supporting
confidence: 60%
“…43 However, the transition of IHCA into HCC and thus tumor initiation is not frequently found. 47 In the present study, we observed a reduction in the DENinduced HCC load in gp130…”
Section: 43supporting
confidence: 60%
“…This protective role of E2 in the gender disparity in hepatocarcinogenesis is recognized in recent years, and several investigations have attempted to address the importance of E2 in the pathogenesis of HCC. [3][4][5]8 Naugler et al 5 showed that E2 inhibited the release of IL-6 from Kupffer's cells, which further reduced the risk of cancer in female mice in diethylnitrosamine-induced hepatic carcinogenesis. Subsequently, Yang et al 21 showed that E2 suppressed hepatic tumor growth via regulating the polarization of infiltrating macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…2 The remarkable gender disparity observed in the incidence of HCC suggests that the sex steroid hormone estrogen may elicit a protective effect against this disease. [3][4][5] The biological functions of 17β-estradiol (E2), a major form of estrogen, are mainly mediated by its two specific estrogen receptors, ERα and ERβ. The role of ERα in carcinogenesis has been widely investigated and elucidated, whereas ERβ was first identified in 1996 (ref.…”
mentioning
confidence: 99%
“…Lower estrogen activity, either caused by menopause or oophorectomy, is a risk factor for female HCC. 25 We recently showed decreased estrogen receptor-␣ protein in many female HCCs, 26 which could be caused by a mechanism regulated by microRNA-18a. 27 Moreover, Naugler et al demonstrated that estrogens could protect hepatocytes from malignant transformation via down-regulation of interleukin-6 secretion from Kupffer cells.…”
Section: Discussionmentioning
confidence: 99%